Acellular bovine pericardium matrix in immediate breast reconstruction compared with conventional implant-based breast reconstruction. (September 2021) - Wang, S.; He, S.; Zhang, X.; Sun, J.; Huang, Q.; Liu, J.; Han, C.; Yin, Z.; Ding, B.; Yin, J.
Abstract: Background: Acellular Bovine Pericardium Matrix (ABPM) is a new material in implant-based breast reconstruction (IBBR). Few studies have reported on its outcome and complications worldwide and most studies were without a control group. Our aim was to compare its use in IBBR with the other two conventional implant-based reconstruction methods. Methods: A retrospective review of patients undergoing IBBR from January to December 2018 was performed. Patients were assigned to the ABPM-assisted IBBR (group A), latissimus dorsi-assisted IBBR (group B) and two-stage IBBR (group C). Patients' post-operative complications, cost-effectiveness and Quality of Life were compared. Results: 100 patients with 100 breasts were included in the study. No complications occurred in group C ( n = 11). No significant differences were noted between group A ( n = 44) and group B ( n = 45) in terms of overall complications (9.1% vs 11.1%, p = 0.973). Group B had the longest operative duration (310.8 ± 62.3 min, p <0.001). The cost of hospitalization forthe three groups was 8051.3 ± 849.2, 7566.0 ± 1172.7 and 7896.5 ± 1762.2, respectively ( p = 0.128). The postoperative Breast-Q scores were similar across the three groups. Conclusions: ABPM demonstrated acceptable complication rates, cost-effectiveness and quality of life outcomes when compared to LD-assisted IBBR and two-stage IBBR.